Corporate fraud and accounting firm involvement: Evidence from China - Jun Wang; Duo Wang (Journal of Risk and Financial Management, 2022)
In some cases, accounting firms and individual auditors will be punished by the China Securities Regulatory Commission (CSRC) for involvement in the violations of their client companies. Taking the enforcement actions against listed companies and accounting firms of the CSRC from 2006 to 2019 as a research sample, this paper manually sorted out the specific characteristics of corporate fraud and empirically examined the regulatory authorities' supervision tendency to auditors. The results show that accounting firms are more likely to be involved when their client companies' fraudulent practices affect financial statements, occur during the IPO process, and continue for a longer period of time. Income statement manipulation and higher fraud amounts also increase the probability of accounting firms being sanctioned. Further analyses show that regulators' supervision intensity is increasing over time, and they impose penalties on auditors based on the severity of corporate fraud; however, the intensity and differentiation of the sanctions are still insufficient. This study expands relevant research on accounting firm sanctions and provides empirical evidence for further improvement of audit industry supervision in an emerging market.
Keywords: 650; accounting firm involvement; administrative supervision; audit failure; corporate fraud